Investigation of the physicochemical, bacteriological, and sensory quality of beef steaks held under modified atmosphere packaging and representative of different ultimate pH values. (April 2021) - Yang, Xiaoyin; Wang, Jing; Holman, Benjamin W.B.; Liang, Rongrong; Chen, Xue; Luo, Xin; Zhu, Lixian; Hopkins, David L.; Zhang, Yimin
Abstract: The objective was to evaluate the effect of packaging conditions on bacteriological and biochemical changes in beef steaks classified here, as normal ultimate pH (pHu; 5.40–5.79), intermediate pHu (5.80–6.09) or high pHu (≥ 6.10). Steaks were packaged in vacuum packaging (VP) and modified atmosphere packaging with high oxygen (HiO2 -MAP) or carbon monoxide (CO-MAP). Headspace, bacterial counts, total volatile basic nitrogen, pH, purge loss, surface color, lipid oxidation, and sensory attributes were monitored over a 14-day storage period at 2 °C. HiO2 -MAP and CO-MAP of high pHu steaks resulted in a bright red color even when observed to be spoilt. Reduced purge loss and lipid oxidation, as well as increased sensory acceptability were observed for steaks with elevated pHu. Higher pHu was also accompanied by an acceleration of microbial proliferation. Of all packaging types investigated, CO-MAP exerted the best preservation, regardless of pHu and based on its antibacterial and antioxidant properties. Highlights: CO-MAP had the best preservation due to its antibacterial and antioxidant effect. The bright red color achieved with CO-MAP and HiO2 -MAP could mask spoilt DC beef. DC beef showed low lipid oxidation, purge loss and shear force even under HiO2 -MAP. Tenderness, juiciness, and overall liking scores increased as pHu elevated.